2016
DOI: 10.1099/ijsem.0.001121
|View full text |Cite
|
Sign up to set email alerts
|

Phytohabitans kaempferiae sp. nov., an endophytic actinomycete isolated from the leaf of Kaempferia larsenii

Abstract: A novel endophytic actinomycete, designated strain KK1-3 T , which formed single spores and long chains of spores (more than 10 spores) was isolated from surface-sterilized Kaempferia larsenii leaf collected from Ubon Ratchathani province, Thailand. The isolate contained L-lysine, meso-diaminopimelic acid and hydroxyl diaminopimelic acid in the cell-wall peptidoglycan. The whole-cell sugars included glucose, mannose, rhamnose, ribose, galactose and xylose. The characteristic phospholipids were phosphatidyletha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Physiological and biochemical characteristics were examined as described previously [ 59 , 60 ]. Each test was performed on three replicates.…”
Section: Methodsmentioning
confidence: 99%
“…Physiological and biochemical characteristics were examined as described previously [ 59 , 60 ]. Each test was performed on three replicates.…”
Section: Methodsmentioning
confidence: 99%
“…Results suggest 44 genera of Actinobacteria were detected in clones while actinomycetes belonging to only 16 genera were isolated. Furthermore, the genus Phytohabitans which presently comprised only five species isolated from plant samples 24,30,38 were detected only in the clone library. Kibdelosporangium strains isolated in the past from both plant roots and rhizospheric soils were not isolated in this case although those 16S rRNA genes were detected (8.8%).…”
Section: Endophytic Bacteria In Plantsmentioning
confidence: 99%
“…During this study, a novel species Phytohabitans kaempferiae was reported, which is an endophytic actinomycete isolated from the leaf of Kaempferia larsenii [24]. Although the whole genome has yet to be sequenced, the analysis will also reveal further potential of the genus because different species, in general, harbor specific PKS and NRPS pathways, as shown in this and our previous studies on actinomycetes [15][16][17].…”
Section: Discussionmentioning
confidence: 69%